Association of Black Women’s Perceptions of the Sex Ratio to Their Attitudes Toward and Experiences of Intimate Partner Violence - Vanterpool, Karen B. (Violence against women, 2022)
This study explores how perceptions of the availability of male dating partners (sex ratio) affect heterosexual Black women’s tolerance and experiences with intimate partner violence (IPV). Evolutionary behavioral models suggest that when the sex ratio is high (more available men than women), violence against women is more likely to occur, whereas the Guttentag–Secord model suggests that when there is a surplus of men, violence against women is less likely to occur. Testing these theories, results show perception of a high sex ratio was significantly positively associated with experiences of IPV in the past 12 months and more tolerant attitudes toward IPV.